Bellucia pentamera Naudin Potency as a Natural resource of Medicine; Change its Status From Invasive to Useful plant - H Marisa; Salni (International Journal of Ecophysiology, 2023)
A Regulation from Indonesian Ministry for Environmental and Forestry, number P.94/MENLHK/SETJEN/KUM.1/12/2016 categorizes Bellucia pentamera Naudin is characterized as an invasive plant, that need a strict management and control. However, many recent studies show this species has many useful as source of traditional medicine recipes. characters that indicate the new status of Bellucia pentamera as useful medicinal plant. Green-immature fruit of Bellucia pentamera contains 2.210 mg/100 g of vitamin C, while the yellow-ripening one has higher, up to 3.500 mg/100 g of. Vitamin C is generally known as an effective threat for many symptoms. Therefore, it could be consider to put Bellucia pentamera as a potential plant for medicinal purpose. Organoleptic test of fruits sauté, found 60 % respondents said the fruit sauté is generally taste as sauté, and 40 % of them said rather delicious.